أثر تحليل البيانات الضخمة في موثوقية المعلومات المحاسبية "دراسة ميدانية" (Damascus University Journal for the economic and Political sciences, 2024)
The study aimed to demonstrate the impact of big data analysis on the reliability of accounting information in the Syrian private banks listed on the Damascus Stock Exchange, by showing the impact of (the availability of infrastructure, the availability of qualified human cadres, the availability of management support) on the reliability of accounting information.The descriptive analytical method was relied on, and the study population included workers in the fourteen listed banks in the Damascus Securities Exchange, distributed into eleven conventional banks and three Islamic banks. in the mentioned banks.The questionnaire was relied on as a tool for data collection and electronic distribution, and then (87) valid questionnaires were analyzed using the statistical program SPSS, using simple and multiple linear regression.The study concluded that there is a significant effect of the analysis of big data on the reliability of the accounting information of the Syrian private banks listed on the Damascus Stock Exchange.
Keywords: big data analysis; reliability of accounting information